2005
DOI: 10.1111/j.1399-5618.2005.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence for persistent abnormalities in amygdala volumes in adolescents and young adults with bipolar disorder

Abstract: Objectives-Abnormalities in volumes of the amygdala have been reported previously in adolescents and adults with bipolar disorder (BD). Several studies have reported reduced volumes in adolescents with BD; however, both decreases and increases in volumes have been reported in adults with BD. Understanding of potential developmental contributions to these disturbances in morphology of the amygdala has been limited by the absence of longitudinal data in persons with BD. Here we use a within-subject longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
3
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 47 publications
9
77
3
5
Order By: Relevance
“…The amygdala is important for the interpretation of emotional meaning, and it has been reported that patients with depression have impaired function during emotional tasks involving the amygdala (Sheline et al, 1998) and that patients with mood disorders consistently display volumetric reductions in the amygdala with imaging studies (Sheline et al, 1998;Mervaala et al, 2000;Blumberg et al, 2003;Blumberg et al, 2005;Chang et al, 2005;Rosso et al, 2007). These changes have been attributed to a decrease in glial cells, with both astrocytes and oligodendrocytes being reduced in number without a concomitant loss of neurons (Bowley et al, 2002;Gosselin et al, 2009;Altshuler et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The amygdala is important for the interpretation of emotional meaning, and it has been reported that patients with depression have impaired function during emotional tasks involving the amygdala (Sheline et al, 1998) and that patients with mood disorders consistently display volumetric reductions in the amygdala with imaging studies (Sheline et al, 1998;Mervaala et al, 2000;Blumberg et al, 2003;Blumberg et al, 2005;Chang et al, 2005;Rosso et al, 2007). These changes have been attributed to a decrease in glial cells, with both astrocytes and oligodendrocytes being reduced in number without a concomitant loss of neurons (Bowley et al, 2002;Gosselin et al, 2009;Altshuler et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These have implicated cortical [54] and subcortical [51,52,55] areas as having structural alterations. Studies in adolescent and first-episode bipolar disorder [56] and one longitudinal study of adolescents [55] demonstrate smaller amygdalae and smaller [51] or no change in hippocampus in adolescent bipolar disorder, which differs from the previously described findings of enlarged amygdalae in adults. In examining prefrontal volumes, earlier pediatric studies failed to detect any difference; however, a more recent study in children and adolescents using a more sensitive, voxel-based, morphometric, automated technique showed decreased volume of DLPFC and amygdala and specific striatal structures [54].…”
Section: Pediatric Bipolar Disordermentioning
confidence: 99%
“…197 Other recent findings indicate decreased bilateral OFC in BD adolescents. 202 Given the discrepant findings between BD children and adolescents and BD adults in key areas such as the amygdala, further study must be done to determine possible differences in PFC volumes of those with early vs late onset and/or diagnosis, to characterize the effects of chronic mood stabilizer treatment on regional brain structure, and to track change over development within the context of possible compensatory mechanisms (including early treatment).…”
Section: Pediatric Bipolar Disorder and High-risk Populationsmentioning
confidence: 99%